PENDAMPINGAN PROSES KREATIF DALAM MENULIS CERPEN MENGGUNAKAN BLOGSPOT PADA SISWA KELAS XI SMAN KABUH JOMBANG - Fitri Resti Wahyuniarti; Nanda Risky Ardhana; Amelia Septiana; Muhammad Saibani Wiyanto (Nusantara Hasana Journal, 2025)
SMAN Kabuh offers significant opportunities in education, particularly in innovative and technologically adaptive learning processes. SMAN Kabuh, a state educational institution, has the potential for further development due to its excellent facilities and infrastructure. The short story writing learning process still uses traditional methods that do not utilize IT technology, such as Blogspot, which is easy to create and access for students. To develop students who can write short stories, this process approach prioritizes the writing process in its learning. These stages or processes are implemented to instill the principle of respecting the process undertaken by students until completion of their work. The creative process is more difficult than simply a seemingly effortless process. The stages of the creative process are: preparation, elaboration, illumination, and verification. The methods used in the community service activity, entitled "Mentoring the Creative Process of Writing Short Stories Using Blogspot for Grade XI Students of SMAN Kabuh Jombang," included lectures, discussions, questions and answers, and practice/mentoring. This community service activity successfully improved students' creative writing literacy skills and digital skills through the medium of blogs. Using a creative process approach, students are guided to enjoy and appreciate each stage of short story writing, from planning to publication. Twenty-six students successfully created personal blogs and published their short stories, reflecting the program's success in developing students' imagination, expression, and self-reflection through storytelling. The program also equips teachers with innovative learning strategies, combining technology and creativity, making writing instruction more relevant to current developments.